Piersi w świętości… - Regiewicz, Adam (Tematy i Konteksty, 2017)
The analysis of medieval hagiographic stories bring an interesting reflection on the role and significance of female breasts in faith transmission. Their presence in cultural transmission, despite common conviction about absence of erotic motives in the culture of the Middle Ages is quite widespread. It is strongly connected with biblical tradition in which the breasts become a symbol of mother-hood and at the same time of youth and joy expressed by wine. Simultaneously in early Christian tradition female breasts become the mark of martyrdom. Mythical narration emerging in this way combines milk and blood as life-giving juices which may be sucked by a “child of God”.